Reverse Logistics Supply Chain Network Design: Models and Issues - Luitel, Prabesh; Lieckens, Kris; Vandaele, Nico (International Journal of Supply Chain Management, 2014)
Environmental concern from customers, government and international institution such as EU and others urge the manufacturer to take back their products after use. We address eight different network design configurations from which the manufacturer can select the design for their reverse logistics system based on their requirements. The dominant literatures on reverse logistics network design are based on mixed integer program model and few center around subjective decision making approach like analytic hierarchy process, but none has integrated both approaches in the same context. In this paper, we explore two different methodologies- mixed integer program model and analytic hierarchy process, for the same business scenario using the real data and further conduct the extensive sensitivity analysis for three levels of volume i.e. high, medium and low. In addition, we discuss practical implications of our findings from two different methodologies and we provide insights on network design for reverse logistics system.